Herramienta administrativa- tecnológica y su incidencia en la operatividad de los servicios de la empresa Martinizing año 2014-2015, Propuesta de tecnología CRM. - Jaramillo Ospina, Katty Leonela (2015)
This letter contains the investigative process that was developed for the company Martinizing city of Guayaquil, with the theme management tool - technology and its impact on the operation of the services of the company Martinizing 2014 - 2015. Proposal of CRM technology, aspects that should be the company to retain customers, based on knowledge of customer needs were analyzed, value-added solutions to a level of excellence that meets thus ensure their loyalty and maximize was given the value generated by each. The methodology was applied to collect the information, he relied on the use of techniques such as observation records and obtaining in this last survey, primary information provided by customers and company employees also interview the administrator. The results allowed identifying aspects necessary to design the administrative-technological tool that served to customer loyalty to the company, the service module being customer indicated to achieve and the first run because of the budget available to the company Currently, the tool has the ability to expand in the future to the remaining two modules are sales and marketing, allowing them to control internal and external logistics processes that are involved in the financial department, human talent and marketing.